2005
DOI: 10.1007/s10816-005-5666-4
|View full text |Cite
|
Sign up to set email alerts
|

What is a Burin? Typology, Technology, and Interregional Comparison

Abstract: Classification of artifacts has long marked a significant edge between theory and practice in archaeology. While considering classification to be a necessary methodological device, most practitioners also recognize that it carries with it built-in assumptions. This essay approaches the issue by way of a specific stone tool type from Old World sites: the burin. By asking "what is a burin?" the study shows the need to reconsider typologies to reflect changes in research questions and progress in dating methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Microscopic analyses on hundreds of burins from the Moravian sites of Pavlov and Willendorf (both spanning the LGM) revealed that the burin was more a byproduct of blade production and served also as an all-purpose pocketknife, with nearly half the use-wear traces consistent with scraping and/or cutting organic materials such as animal hides (Tomášková 2005). Hide-working is identified as the predominant function of both scrapers and blades at Pavlov I but, consistent with predictions of the thermal model, the inferred working motions for these tool types were quite different: scrapers were used almost exclusively in a transverse (i.e., hidescraping) direction while blades were used almost exclusively in a longitudinal (i.e., hide-cutting) direction (Šajnerová-Dušková 2007, pp.…”
Section: Upper Paleolithicmentioning
confidence: 99%
“…Microscopic analyses on hundreds of burins from the Moravian sites of Pavlov and Willendorf (both spanning the LGM) revealed that the burin was more a byproduct of blade production and served also as an all-purpose pocketknife, with nearly half the use-wear traces consistent with scraping and/or cutting organic materials such as animal hides (Tomášková 2005). Hide-working is identified as the predominant function of both scrapers and blades at Pavlov I but, consistent with predictions of the thermal model, the inferred working motions for these tool types were quite different: scrapers were used almost exclusively in a transverse (i.e., hidescraping) direction while blades were used almost exclusively in a longitudinal (i.e., hide-cutting) direction (Šajnerová-Dušková 2007, pp.…”
Section: Upper Paleolithicmentioning
confidence: 99%
“…Many of these problems can be explained by historical factors, including political and linguistic considerations (Tomášková 2003;Roberts & Vander Linden 2011). The quantity and quality of archaeological work that has been carried out across Europe also varies widely, and the biased distribution of known sites affects our understanding of material variation within the archaeological record.…”
Section: The Shortcomings Of the Current Systemmentioning
confidence: 99%
“…Even if we disregard problems of inter-observer variability, there are strong differences between the various schools of lithic analysis. Contrasts can be made between approaches that emphasise technology or typology, chaîne opératoire studies, reduction sequences or attribute analyses, and those that are more or less quantitative or qualitative (Shott 2003; Tomášková 2005; Scerri et al . 2016; Hussain 2018).…”
Section: The Remediesmentioning
confidence: 99%
“…In the lithic studies literature there is a general division between typological studies and technological studies (e.g. Minzoni-Deroche 1985;Callahan 1987;Lindgren 1998;Inizan et al 1999;Andrefsky 2001;Tomášková 2005;Ballin 2008); typological studies are generally geared towards results -the finished artefact; these 'finished' artefacts also include core 'types' in typologies. Technological studies are not restricted to typing 'tools', but concern an entire assemblage, including the 'waste' or 'debitage'/'debris', to understand the mode of manufacture.…”
Section: Background To Quartz Researchmentioning
confidence: 99%